Socioeconomic Differences in Adolescent Sexual and Reproductive Health : Family Planning - Yarger, Jennifer (World Bank, Washington, DC, 2015)
Adolescent sexual and reproductive health (ASRH) is one of five areas of focus of the World Banks reproductive health action plan (RHAP) 2010-2015, which recognizes the importance of addressing ASRH as a development issue with important implications for poverty reduction. Delaying childbearing and preventing unintended pregnancies during adolescence has been shown to improve health outcomes and increase opportunities for schooling, future employment, and earnings. This brief highlights the limited contraceptive use among adolescent women and the socioeconomic disparities in family planning among this population. The results indicate the importance of investing in programs aimed at increasing access to safe and effective contraceptive methods and expanding adolescents knowledge of modern contraception, particularly among adolescent women in rural and poor areas and or those with limited or no education, regardless of marital status. Continued investment should be made in female education and empowerment as a means to reach economic development goals, as well as related goals, such as an increase in adolescent contraceptive use to reduce the incidence of unplanned pregnancies.